A Review on Uranium Mineralization Related to Na-Metasomatism: Indian and International Examples - Priyanka Mishra; Manju Sati; Rajagopal Krishnamurthi (Geosciences)
Uranium mineralization related to Na-metasomatism is known as Na-metasomatite or albitite-type. They represent the fourth-largest uranium resource globally and constitute fifty thousand tons of U resources. The present work gives details about well-known Na-metasomatic uranium occurrences worldwide in terms of structures, metasomatic stages, geochemical characteristics, fluid inclusions, and compositions of stable isotopes. The host rocks are granite, granitoid, and metamorphosed volcano-sedimentary rocks, and these rocks experienced two/three deformational stages. U mineralization is mainly confined to faults and characterized by granitic intrusive, cataclasis, mylonitization, and albitization. The albitized rocks exhibit two to three metasomatic and late hydrothermal stages. The first stage is marked by the replacement of pre-existing host minerals during a ductile shear regime. The second stage is related to U mineralization contemporaneous with the brittle deformation. The albitized rocks exhibit depletion in Si, K, Ba, and heavy rare-earth elements relative to the host rocks and enrichments in Na, Ca, U, Zr, P, V, Sr, and light rare-earth elements. U-enrichment is positively correlated with Na, Mo, Cu, and high-field strength elements. The pressure–temperature (P-T) conditions of U mineralization are considered to be epithermal and mesothermal. Fluid inclusion studies indicate that the mineralizing fluids were rich in Na+, Mg2+, Cl−, CO2, H2O, F−, and PO43− and meteoric–magmatic derived. The geological processes responsible for the genesis of Na-metasomatic U deposits of the North Delhi Fold Belt (India) are comparable with some international examples, i.e., Australia, Ukraine, Cameroon, Brazil, Guyana, China, and the USA.